Association between uncoupling protein 2, adiponectin and resting energy expenditure in obese women with normal and low resting energy expenditure. (1st February 2018) - Taghadomi Masoumi, Zahra; Eshraghian, Mohammad Reza; Hedayati, Mahdi; Pishva, Hamideh
Abstract: Obesity is recognized as the most prevalent metabolic disease worldwide. Decreases in energy expenditure may increase risk of obesity. One of the key regulators of energy balance is uncoupling protein2 (UCP2), a transporter protein presents in mitochondrial inner membrane. Moreover, adiponectin is the most abundant adipocytokine, it may play a role in energy metabolism and gene expression of UCP2. The aim of this study was to investigate potential associations between the level of uncoupling protein 2 and adiponectin and their relationship with REE (Resting Energy Expenditure) in obese women with normal and low resting energy expenditure. A total of 49 subjects (women, 25–50 years old), were included in current study, 16 subjects with BMI > 30 and low resting energy expenditure, 17 subjects with BMI > 30 and normal resting energy expenditure and 16 non-obese subjects as a control group. Anthropometric, body composition parameters and resting energy expenditure were measured. Plasma adiponectin, UCP2 protein and total protein in PBMC were determined. Measured resting energy expenditure in obese subjects with low REE was significantly lower than other groups. Plasma adiponectin in the obese subjects with low REE was significantly lower compared to normal weight group. There was a significant relationship between 'UCP2 protein/Total protein' ratio and plasma adiponectin in obese group with low REE and in three groups when we pooled. There was a significant association between REE and plasma adiponectin in three groups when we pooled. There was a significant association between plasma adiponectin and REE. Moreover, there was a significant relationship between UCP2 and REE.